Perancangan Permainan Gelembung Huruf (Tokoh Wayang) Berbasis Sistem Operasi iOS Menggunakan Gamesalad - Adhitama Ksatriya Nugraha; Kodrat Iman Satoto; Rinta Kridalukmana (Jurnal Teknologi dan Sistem Komputer, 2014)
Currently, the globalization and modernization of the country make us forget the traditional culture. Not surprisingly, more people are not familiar with puppet , let alone moved to preserve it. Therefore, in this era get involved use of mobile devices such as smartphones as the most efficient tool as interactive learning media. Now, the use of smart mobile devices are no longer limited by age, therefore developers will try to exploit this as a media that can be used for interactive learning.